Suicidal Pattern of Decapitation Injury and Associated Limb Injury in Railway Track Traumas: A Case Series - Khilji, Sahajad; Jain, Ashish; Kurveti Verma, Priyamvada; Baraw, Rajendra (International Journal of Medical Toxicology and Forensic Medicine, 2022)
Suicide by high-speed railway track trauma with complete decapitation is a rare event; however, it is well known and reported in the scientific literature. The authors analyzed 5 cases of suicide with complete decapitation along with upper limb amputation or severe injury by high-speed mainline train subjected to medico-legal autopsies at the Department of Forensic Medicine and Toxicology, Gandhi Medical College, Bhopal between 2019 and 2021. Upper limb injury is considered because of scientific reasons that they have been amputated along with decapitation. Personal, circumstantial, autopsy, and toxicological data and thevictim’s psychical profile were analyzed, and factors like the type of injury, the vital reaction of wound edges, absence of any signs of defense, alcohol, and drug consumption were also considered.